Polemik Transendensi Tuhan Antara Mutakalim dan Salafi Kontemporer dalam Teks Al-‘Aqīdah al-Ṭaḥāwiyyah: The Polemic of God's Transcendence Between the Mutakallimūn and Contemporary Salafis in the Text of Al-‘Aqīdah al-Ṭaḥāwiyyah - Nur Shadiq Sandimula; Djody Firmansyah (University of Darussalam Gontor, Indonesia, 2025)
Tanzīh is an essential concept in Islamic theology that demonstrates the transcendence of God from any resemblance to all creatures. One of the primary texts of Islamic theology is al-‘Aqīdah al-Ṭaḥāwiyyah by Abu Ja'far al-Thahawi, which is acclaimed unanimously by all Sunni Muslims. However, there has been debate among scholars regarding the establishment of the concept of tanzīh, notably between the Mutakallimūn and Contemporary Salafis. This study aims to examine the concept of tanzīh in the text of al-‘Aqīdah al-Ṭaḥāwiyyah. The method used in this study is qualitative with descriptive-theological analysis through a content analysis approach. The results of this study indicate that all Sunni groups have unanimously approved the text of al-Thahawi’s creed. However, in claiming legitimate representation to explain the text, there is a debate between the Mutakallimūn and the Salafis, both of whom claim to be Sunni. The central disagreement lies in using terms containing the meaning of contingency (ḥawādith) in linguistic terms regarding the Attributes of God. For the Mutakallimūn, any text by al-Thahawi that demonstrates the sanctification (tanzīh) of God's attributes from the categories of creatures (ḥawādith) is accepted affirmatively with expositions that support the content of the text. Meanwhile, the Salafi school polemically contests these texts because al-Thahawi uses ambiguous and multi-meaning terms (mujmal) that imply a denial of the Attributes of God as explicitly mentioned in the Qur’an and Hadith.